Bank Loan Loss Provision Decisions: Empirical Analysis of U.S. Banks and UK Banks - HUNG, RUO-WEI (2012)
This paper investigates and compares the determinants of loan loss provisions in the samples of U.S. and UK banks using 3135 bank-year observations from U.S. and 73 bank-year observations from UK. The explanatory variables of in our regression model include bank specific variables, such as earnings before taxes and provisions, total loans and so on and the macroeconomic variable, GDP growth. UK banks data supports the earnings management hypothesis, but fails to support the capital management hypothesis in this study. Nevertheless, the empirical result with respect to U.S. banks fails to support the earnings management hypothesis, but supports the capital management view. Finally, empirical result also proves a negative association between GDP growth and loan loss provisions in UK banks, while samples of U.S. banks fail to support this relationship.